Cultural Barriers to Community Participation in Drug Control: A Case Study of a Village in Kanchanaburi Province - Lortanapaisan, Tanaroj (Interdisciplinary Journal of Humanities Studies, 2025)
This study aims to (1) explore the patterns of community participation in addressing drug-related problems, (2) analyze the cultural factors and values that hinder community involvement, and (3) explain the relationship between social structures, intra-community relationships, and the behavior of indifference towards drug problems. A participatory qualitative research methodology was employed, involving in-depth interviews, participatory observations, and focus group discussions with community members, local leaders in a village in Kanchanaburi Province.The findings indicate that community participation is limited to awareness and discussions within families or close-knit groups, with a lack of proactive actions or reporting to government authorities. Cultural factors, such as the values of “not wanting to interfere with others' business” and “keeping a pleasant exterior,” contribute to the silence of villagers, even when they are aware of drug trafficking in the area. Reflections from community members include phrases like “I know, but I won't speak out; it might cause trouble,” or “I see it, but it's not my business.” This indifference is closely tied to the social structure within the community, which emphasizes maintaining face, harmony, and avoiding conflicts with relatives or close associates.The research suggests that promoting community participation should align with the local cultural context. A model could be developed that utilizes natural leaders or trusted relational mechanisms, such as extended family networks, as intermediaries for informal communication and information sharing, fostering community empowerment without violating traditional cultural structures.